The Influence Of Work Discipline And Work Experience On The Performance Of Security Section Employees At PT SWAT Tasikmalaya - Nurzehan, Salma Hurilan; Sutrisna, Arga; Risana, Dudu (Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of work discipline and work experience on employee performance at PT Swat Kota Tasikmalaya. The method used was quantitative with a research sample of 40 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Work Discipline and Work Experience simultaneously have a positive and significant effect on Employee Performance. Work Discipline partially has a significant effect on Employee Performance. Work experience partially has a significant effect on employee performance.